Factors Influencing Behavior and Financial Welfare of MSMEs - Maria Widyastuti; Y. Budi Hermanto; Amanda Wahyu Astuti (Widya Cipta: Jurnal Sekretari dan Manajemen, 2025)
The aim of this research is to test financial literacy, self-control, optimism, deliberative thinking in determining the value of financial behavior and well-being. This research is explanatory/associative by testing hypotheses. The research population is MSME actors in East Java (Sidoarjo, Malang, Pasuruhan, Gresik), with a sample of 200 MSME actors, data collection using the purposive sampling method. The results of data processing with the help of the SmartPls analysis program show that financial literacy, self-control, optimism and deliberative thinking have a significant but weak direct and indirect influence on financial behavior and financial well-being. The results of this research provide meaning that financial literacy, self-control, optimism and deliberative thinking have a strategic role in explaining why the financial behavior and well-being of MSMEs is getting better and developing. So that the understanding of MSME players regarding: financial literacy must always be developed, self-control means that when spending money must be based on careful consideration, a spirit of optimism needs to be fostered because it will give rise to confidence that the results of the efforts made will be positive, profitable and as expected. Meanwhile, deliberative thinking is a planned, clear, considered decision-making process that influences personal decision making.